Formulation and Evaluation of Nanosponge Hydrogel for Transdermal Release of Curcumin - N Pathan, Albina; Shinde, Jitendra; Bhosale, Ashok (Journal of Neonatal Surgery, 2025)
Curcumin is a hydrophobic component that shows anti-cancer, antioxidant properties but it faces problem for its bioavailabilty .To overcome this problem Curcumin is encapsulated into a nanosized polymeric structure called as nanosponge.This polymeric encapsulation provides sustained and control release of curcumin from its hydrogel matrix. Encapsulation was done with the help of various concentration of Ethyl cellulose as a polymeric matrix and Polyvinyl Alcohol as a stabilizer. A 32 factorial design was employed to investigate effect of EC:HPMC K100 and PVA on drug entrapment efficiency,drug release .Resuls indicated that wehe we reduce the concentration of Ethyl cellulose Drug entrapment efficiency decreases and drug release increases.So,it highlights balance between polymer concentration and Drug release. Then the optimized nanosponge formulation was incorporated in a hydrogel matrix by varying concentration of Carbopol 940 and investigating its effect on spreadability,viscosity and permeation.So we can tailor the drug release and spreadibility of the hydrogel matrix by changing the concentration of Carbopol. So the study reveals that careful modification of the formulation factors significantly affect the transdernal release of curcumin loaded nanosponge hydrogel.This system gives a promising approach of controlled and sustained release of curcumin in breast cancer through a non-invasive strategy and less side effects.